The American College of Critical Care Medicine Clinical Practice Parameters for Hemodynamic Support of Pediatric and Neonatal Septic Shock: Executive Summary - Davis A.L. (Lippincott Williams and Wilkins, 2018)
10.1097/PCC.0000000000001259